Multivarate calibration of fourier transform spectra in determining the malonaldehyde as a TBA reactive substance (TBARS) in palm olein - Mirghani, Mohamed Elwathig Saeed; Che Man, Yakoob; Selamat, Jinap; Baharin, B. S.; Bakar, Jamilah (Springer Berlin, 2001)
Fourier transform infrared (FTIR) spectra of palm oil samples between 2900 and 2800 cm–1 and 1800 and 1600 cm–1 were used to compare different multivariate calibration techniques for quantitative determination of their thiobarbituric acid-reactive substance (TBARS) content. Fifty spectra (in duplicate) of palm oil with TBARS values between 0 and 0.25 were used to calibrate models based on partial least squares (PLS) and principal components regression (PCR) analyses with different baselines. The methods were compared for the number of factors, coefficients of determination (R2), and accuracy of estimation. The standard errors of prediction (SEP) were calculated to compare their predictive ability. The calibrated models generated three to eight factors, R2 of 0.9414 to 0.9803, standard error of estimation (SEE) of 0.0063 to 0.0680, and SEP of 1.20 to 6.67.